Influence of potassium iodide in polyvinyl alcohol-based gel polymer electrolyte for efficiency enhancement of dye-sensitized solar cells - Abdul Aziz, Mohd Fareezuan; Mohd Abid, Mohd Asyadi 'Azam; S. N. F. Yusuf; M. H. Buraidah; A. K. Arof (Springer Science and Business Media B.V, 2022)
This study investigates the impact of small cations on improving conductivity and efficiency of dye-sensitized solar cells (DSSCs). The work includes preparation and characterization of polyvinyl alcohol-based gel polymer electrolytes (GPEs) containing tetramethyl ammonium iodide (TMAI) and potassium iodide (KI) salts. The degree of crystallinity of the GPEs has been determined from x-ray diffraction (XRD). From electrical impedance spectroscopy (EIS), the gel polymer electrolyte with only TMAI salt exhibits a conductivity of 1.72 mS cm−1. On addition of KI salt, conductivity increased up to a maximum of 7.87 mS cm−1 for the GPE comprising 70 wt. % KI. The dye-sensitized solar cells (DSSCs) with GPE comprising 100 wt. % TMAI – 0 wt. % KI exhibits a short-current density, Jsc of 6.60 mA cm−2 and open-circuit voltage, Voc of 0.56 V. The fill factor, ff, and efficiency, η, obtained are 79% and 2.92%, respectively. The existence of a small cation K+ in the GPE enhances DSSCs performance with GPE consisting of a 3:7 weight ratio between TMAI and KI exhibits Jsc of 11.30 mA cm−2 and Voc of 0.60 V. The acquired fill factor, ff, and efficiency, η, are 74% and 5.02%, respectively.